Prioritization of the Best Online Platform for MSMEs Using Simple Additive Weighting Method - Sutrisno Sutrisno; Wulandari Wulandari; Vivid Violin; Agung Supriyadi; Muhammad Risal Tawil (Journal on Education, 2023)
Many MSMEs have begun embracing online marketing platforms to sell their products and services in the current digital era. This is because online platforms facilitate MSMEs' access to a larger market and streamline the transaction process. With so many online platforms accessible today, it is tough to determine which is the best for MSMEs. Hence, a decision-making method is required to aid micro, small, and medium-sized enterprises (MSMEs) in identifying the online promotion platform that best meets the evaluation criteria. Using the Simple Additive Weighting (SAW) method, the primary purpose of this study is to aid micro, small, and medium-sized enterprises (MSMEs) in selecting the online platform that best meets their business objectives. The ranking results demonstrate that decision-making processes can be utilized to rank the most effective internet promotion platforms for MSMEs. From the final results, it is determined that the criteria for segmenting consumer reach and ease of use of applications are important in determining online promotion platforms, with the results of platform prioritization indicating that Instagram and Whatsapp chat media continue to dominate as an alternative online promotion platform for MSMEs.